(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A Real Estate Project is a group of people who have a common purpose or objective. A Real Estate Project usually comprises several undertakings which have to be accomplished by a certain date, within a given budget with some expected level of performance. All Real Estate Projects have some well-defined objectives and sufficient resources to complete the required tasks and sub-tasks.The basic objective of a Real Estate Project management is to control the overall Real Estate Project and maximize the use of the limited resources. For this purpose, a team is built in Real Estate Project management in order to increase the efficiency of a Real Estate Project and to control the overall activities of a Real Estate Project. This team includes a Real Estate Project manager and several Real Estate Project engineers.